Analisis Biaya Mutu Dalam Peningkatan Mutu Layanan Kesehatan di Puskesmas Kota Pinang Kabupaten Labuhanbatu Selatan - Anggi Rezkina Nasution; Dewi Rahmadani Wiranata; Dinda Susanti; Yuyun Santika; Yolanda Afifah; Dewi Agustina (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2023)
Quality is something that is operationally fulfilled by the customer. There are many factors that affect service quality. The level of commitment, leadership style, and involvement of all employees also has a significant impact. Quality costs can also be divided into two categories based on measurement: observable quality costs and hidden costs. Research method This serves as a layout to be able to understand the research context broadly and deeply. Because basically every research is scientific in nature, then by conducting a literature review. Efforts to initiate Puskesmas quality can be started by strengthening top management commitment and stakeholder support. It is suggested that health care facilities improve recording of cost information. system, which must include quality costs, so that an annual analysis can be performed to evaluate changes in each quality cost category. Keywords: Cost Quality, Service Quality